Migrations and crises. Cyclical factors in the arrival of Swiss in Argentine (1856-1939) - Zang, Laura Mabel (2023)
The article analyzes the migration of Swiss to Argentina between the second half of the 19th century and the first half of the 20th century. The various short-term factors that led to the mobility of people from the European country to various places in America and especially Argentina are examined. To do this, it addresses, on the one hand, the situation of Switzerland during the 19th and 20th centuries and its configuration as a population-expelling country and, on the other, it studies the mechanisms implemented by Argentina for the attraction of immigrants. At the same time, the continuity of the migratory movement in the interwar period - Missions was the main receiving scenario at this stage - was due to the adoption of restrictive migration policies by other countries until then receiving immigrants.